STIGMA SOSIAL DAN DISKRIMINASI TERHADAP PENDERITA COVID-19: Sebuah Tinjauan Perspektif Maqashid Syari’ah - Rosadi, Miftah; Muttaqin, Muhammad Ngizzul Ngizzul (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
As a country affected by the spread of the corona virus (COVID-19), Indonesia is experiencing an increase in cases every day. This raises the fear for the sake of public fear of this virus increasing. The practice of this fear has led to a negative stigma to discrimination against patients and sufferers of corona (COVID-19). This Study uses a qualitative method by taking data through documentation of several online news with data analysis using content analysis. This study will reveal the phenomenon of discrimination against sufferers of COVID-19 in the perspective of maqashid shari’ah. the findings in this research show that the attitude of giving a negative stigma and discrimination against corona sufferers (COVID-19) is an attitude that is opposed to the manifestation of maslahah which is an essential value of Islamic law, namely maqashid shari’ah. Keywords: Negative Stigma, Discrimination, COVID-19, Maqashid Shari’ah.